Envisioning Mothers: Visualizations and the Invisibility of Motherhood - Jolly, Natalie (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Women in the U.S. and Canada pay a substantial social and economic penalty for becoming mothers. And though the existence of a “motherhood penalty” has been extensively demonstrated, motherhood itself has not been widely recognized as a marginalized identity. In this article, I review several popular visualizations (graphical representations, imagery, infographics, etc.) used to depict inequality and oppression to propose that—despite mothers paying a motherhood penalty—motherhood remains an invisible category in current representations of social inequity. I suggest that by subsuming mothers under the category of “women,” current visualizations obscure how gender discrimination (particularly economic discrimination) results from women’s status as “mothers” rather than their status as “women.” As a result, we miss the central role that motherhood plays in women’s social and economic oppression. Motherhood is rarely recognized as an identity that contributes to women’s inequality, and I argue here that this is partially due to its invisibility in popular visualizations of oppression. As a result, I argue that motherhood should appear as an analytic category in our popular visualization of oppression to increase its visibility as a marginalized identity. Such visibility would increase social justice activism around issues of motherhood and would raise public awareness of motherhood as a significant social identity within the context of oppression and inequality.